Dom/Garachi in Azerbaijan among the Dom Communities in the Middle East and North Africa - Elena Marushiakova; Vesselin Popov (Kulturní Studia)
The countries of the South Caucasus (Azerbaijan, Armenia, and Georgia), along with Turkey, represent the only region in the world where all three main subdivisions of the heterogeneous community historically referred to as “Gypsies” — Dom, Lom, and Roma — have coexisted (or, until recently, coexisted) in close proximity. In Azerbaijan, two distinct Dom communities are currently present: Iranian Dom and Kurdish Dom. While both acknowledge a shared overarching identity, they maintain clear distinctions in their everyday lives. This article presents findings from two field research studies conducted in Azerbaijan, through which a preliminary understanding was developed regarding the territorial distribution, lifestyles, socio-economic status, and complex identity structures of these two Dom communities, as well as their interactions with the Roma and Lom populations. The Azerbaijani case is further contextualised within broader historical and political frameworks, contributing to a more nuanced understanding of the position of Dom communities across the Middle East and North Africa.